Binder and method of manufacture
By mixing biomass pyrolytic oil with thermoplastics to make low-toxic binders, the problem of fossil carbon and toxic substances in the steel industry is solved, and a low-carbon footprint and efficient production of clumps is achieved, suitable for blast furnace replacement Taste.
Patent Information
- Application Number
- CN202380044818.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-08
- Publication Date
- 2025-01-14
AI Technical Summary
The binders used in the existing steel industry are based on fossil carbon and contain toxic compounds such as BTX and PAH, which lead to environmental pollution and require sintering and coking during production, resulting in a high carbon footprint.
Use pyrolytic oil produced by biomass pyrolysis and thermoplastic plastics (such as polyethylene and polystyrene) to make a binder. The pyrolytic oil accounts for 80-90% and plastic accounts for 10-20%, and it is dehydrated. and decarbonization treatment to form a low acidity, low corrosion binder for the production of clumps with low carbon footprint.
It reduces the environment and carbon footprint of the binder, reduces the content of toxic substances, improves the safety and production efficiency of the binder, and the produced clumps have high compressive strength, which are suitable for alternatives in blast furnaces.
Smart Images

Figure BDA0005168129550000051
Abstract
Description
Technical Field
[0001] The present invention relates to a binder for producing briquettes, pellets or any other agglomerated material. The present invention also relates to a method for making said binder and a method for making briquettes using said binder. Background Art
[0002] Steel can currently be produced on an industrial scale via two main manufacturing routes. Today, the most commonly used production route involves the production of pig iron in a blast furnace, a process that relies on two main raw materials: sintered iron ore to be reduced and coke as a reducing agent. These two raw materials require a sintering plant and a coking plant, respectively, both of which are large emitters of CO2 and more global pollutants.
[0003] In order to reduce its environmental footprint, the steel industry is seeking solutions to produce materials with carbon and / or iron without the need for sintering and coking processes.
[0004] For this purpose, new cold-based manufacturing processes are being considered, such as extrusion, briquetting or pelletizing. All of these processes require the use of binders.
[0005] Patent JP 2018-165301 A describes a method in which charcoal briquettes are formed using a binder formed by mixing waste plastic and woody biomass in a solvent made from coal tar.
[0006] However, this binder is based on fossil carbon and contains toxic compounds such as BTX, which is a mixture of benzene, toluene and xylene, and polycyclic aromatic hydrocarbons (PAHs). These are pollutants that have been identified as being highly toxic, mutagenic, carcinogenic, teratogenic and immunotoxic to various life forms.
[0007] There is therefore a need for binders with a reduced environmental footprint, including a carbon footprint.There is also a need for materials to be used in the steelmaking industry with a reduced carbon footprint. Summary of the invention
[0008] This problem is solved by the binder according to the invention, which contains 80% to 90% by weight of pyrolysis oil resulting from the pyrolysis of biomass and 10% to 20% by weight of thermoplastic.
[0009] The adhesive of the present invention may also contain the following optional features considered individually or in all possible technical combinations:
[0010] The thermoplastic is selected from polyethylene, polystyrene, polycarbonate or styrene derivatives.
[0011] - The thermoplastic is expanded polystyrene.
[0012] - The biomass is lignocellulosic biomass.
[0013] The present invention also relates to a method for producing a binder, the method comprising mixing pyrolysis oil produced by pyrolysis of biomass with thermoplastics at a temperature of 150° C. to 220° C. in such a proportion and heating to produce a binder such that the binder contains 80% to 90% by weight of the pyrolysis oil and 10% to 20% by weight of the thermoplastics.
[0014] The manufacturing method of the present invention may also include the following optional features considered individually or in all possible technical combinations:
[0015] - pyrolysis of biomass is carried out at temperatures between 450°C and 700°C,
[0016] - the method further comprises the steps of pyrolyzing the biomass to produce biochar and pyrolysis oil, removing water from the pyrolysis oil so that the final water content in the dehydrated pyrolysis oil is less than 5% by weight, and mixing the dehydrated pyrolysis oil with a thermoplastic in such a proportion to produce a binder that the binder comprises 80% to 90% by weight of the dehydrated pyrolysis oil and 10% to 20% by weight of the thermoplastic,
[0017] - a water removal step is selected from a decantation step, a fractional condensation step and a fractional crystallization step,
[0018] - after the water removal step, subjecting the dehydrated pyrolysis oil to a decarbonization step before mixing with the thermoplastic,
[0019] -Densification of thermoplastics before compounding,
[0020] - Casting the hot binder into a mould to produce a binder ingot.
[0021] The present invention also relates to a method for manufacturing agglomerates, the method comprising the steps of mixing at least one material with a binder according to any one of the following combinations, and subjecting the mixture to a compression step to form agglomerates.
[0022] The agglomerate manufacturing method of the present invention may also include the following optional features considered individually or in all possible technical combinations:
[0023] - the at least one material is selected from coking coal, biochar, iron ore or steelmaking by-products,
[0024] - the material is biochar,
[0025] - The material is rolling mill sludge.
[0026] The invention also relates to a raw material comprising a binder according to the invention and at least one material selected from coking coal, biochar, iron ore or steelmaking by-products.
[0027] Other characteristics and advantages of the invention will emerge clearly from the description of the invention which is given below by way of indication and which is in no way limiting. DETAILED DESCRIPTION
[0028] The binder according to the invention contains 80% to 90% by weight of pyrolysis oil resulting from pyrolysis of biomass and 10% to 20% by weight of thermoplastic.
[0029] The pyrolysis process is the thermal decomposition of a material at elevated temperatures in an inert atmosphere. The pyrolysis of biomass produces biochar or biocoal, pyrolysis gas (or syngas) and pyrolysis oil (also called biocrude oil or bio-oil). The thermal conversion of biomass accomplished under anaerobic conditions allows the removal of volatile organic compounds and cellulose components from the feedstock and produces a solid biofuel having characteristics similar to those of fossil coal.
[0030] In the method according to the invention, the pyrolysis process is preferably carried out at a temperature of 450° C. to 700° C. to maximize the yield of biochar and pyrolysis oil. As an example, the pyrolysis can be carried out using a heated screw, the biomass is loaded into a fuel container and extracted from the container to the pyrolysis screw by a feed screw, where the biomass is heated to a temperature of 450° C. to 700° C. The biochar thus formed is extracted at the end of the screw and stored in a container. The pyrolysis gases are collected by a pipeline to a gas cooler such as a condenser that separates the crude pyrolysis oil from the gas. Microwave-assisted pyrolysis (MAP) can also be used.
[0031] Biomass is a renewable organic material from plants and animals. Biomass sources include wood and wood processing waste (e.g., firewood, wood particles and wood chips, wood and furniture factory sawdust and waste), and black liquor from pulp and paper mills, agricultural crops and waste materials (e.g., corn, soybeans, sugar cane, switchgrass, woody plants and algae), and crop and food processing residues, and also include biogenic materials in municipal solid waste such as paper, cotton and wool products, and food, yard and wood waste, animal excrement and human filth. In the sense of the present invention, biomass can also encompass plastic residues, such as recycled waste plastics such as solid refuse fuel (Solid Refuse Fuel) or SRF.
[0032] In a preferred embodiment, the biomass is lignocellulosic biomass.
[0033] To form the binder, pyrolysis oil is mixed with thermoplastic in such a ratio that the binder contains 80 to 90% by weight of pyrolysis oil and 10 to 20% by weight of thermoplastic, the mixing being carried out at a temperature of 150 to 220°C.
[0034] The thermoplastic is preferably selected from polyethylene, polystyrene, polycarbonate or styrene derivatives, and more preferably expanded polystyrene. Polystyrene can be used in its different forms (expanded polystyrene EPS, compact polystyrene), and recycled polystyrene can also be used. The amount of thermoplastic and pyrolysis oil determines the thermoplastic properties of the adhesive. A thermoplastic higher than 20% by weight produces a bioadhesive that hardens at room temperature, which may then be brittle, while waste thermoplastics less than 10% by weight produce a more malleable bioadhesive at room temperature, which is difficult to store and manage.
[0035] In a preferred method for producing a binder according to the invention, after the pyrolysis of the biomass and before mixing with the thermoplastic, the pyrolysis oil is subjected to a water removal step. Most of the water formed is chemically generated during the pyrolysis process and does not come from the biomass material. This water removal step allows limiting the acidity and corrosion risks of the produced binder and improving the efficiency of the production process of the binder. In fact, the presence of water may slow down production and increase energy requirements.
[0036] This water removal step can be carried out using different techniques, among which are decantation, fractional condensation or fractional crystallization.
[0037] In a preferred embodiment, low-density thermoplastics such as expanded polystyrene (EPS) are subjected to a pretreatment step, which is a densification step, for example a chemical densification step as described in patent WO 1998 023 672, before being mixed with the pyrolysis oil. In a preferred embodiment, the solvent used for the densification step is d-limonene. This allows reducing the volume of thermoplastic to be mixed with the pyrolysis oil in order to reach a suitable binder composition.
[0038] In a preferred embodiment, the hot binder resulting from the mixing is cast in a mold to form an ingot at room temperature. This allows for easier handling and storage of the binder.
[0039] The binder according to the invention can be used to make extruded material, pelletized material, briquette material or agglomerated material. In the method for making agglomerates according to the invention, at least one material is mixed with a binder as previously described and the mixture is subjected to a compression step to form agglomerates. The at least one material can be selected from coking coal, biochar, iron ore or steelmaking byproducts.
[0040] Other manufacturing techniques such as extrusion, pelletizing or agglomeration can be used to produce raw materials using the binder according to the invention and at least one material selected from coking coal, biochar, iron ore or steelmaking by-products. The steelmaking by-product is preferably rolling mill sludge. It may also be iron powder.
[0041] In a preferred embodiment, the biochar produced by the pyrolysis of biomass is mixed with a binder according to the invention comprising pyrolysis oil from the same pyrolysis process and subjected to a briquetting step to produce biochar briquettes. These biochar briquettes can then be charged, for example, into a blast furnace or electric arc furnace, a smelting furnace or a direct reduction furnace as a carbon source.
[0042] In another embodiment, a binder is mixed with oxidized iron ore and biochar and subjected to a pelletizing step to form combined iron-biochar pellets. These pellets can then be subjected to a direct reduction process to reduce the oxidized iron.
[0043] Example 1
[0044] Six binders B1 to B6 were prepared using different main components to be mixed with the thermoplastic.
[0045] Binders B1 to B4 are binders according to the invention and contain 85% by weight of pyrolysis oil produced by pyrolyzing straw, beech, sawdust and pine, respectively, at 450° C. during 45 minutes at a heating rate of about 10° C. / min in a pyrolysis screw apparatus as previously described and 15% by weight of expanded polystyrene (EPS).
[0046] B5 is a binder consisting of 85 wt% coal tar + 15 wt% EPS, and B6 is a binder consisting of 85 wt% coal tar sludge + 15 wt% EPS. B5 and B6 are according to the prior art.
[0047] The production process of the six binders is the same, and the corresponding proportion of oil / coal tar is mixed with EPS at a temperature of 250° C. during 2 hours. The chemical compositions of the six binders are then analyzed, and the results are shown in Table 1.
[0048]
[0049] Table 1 (* Prior art)
[0050] The binders according to the invention (B1 to B4) contain less sulfur, less BTX and less HAP, so they are less harmful to the environment.
[0051] Example 2
[0052] A set of biochar briquettes was prepared using biochar as filler and a binder according to the invention. Beech wood was used as biomass. The resulting pyrolysis oil was mixed with 15% by weight of EPS to form a binder according to the invention. The biochar was pulverized so that the final particle analysis was below 2 mm for at least 70% of the biochar particles. The pulverized biochar was then mixed at a temperature of about 150° C. in a ratio of 80% by weight of biochar, 20% by weight of binder. The mixture was then rolled in a roller press at a hydraulic pressure of about 700 bar to ensure a linear pressure of 3 tons / cm wheel width along a wheel with a width of 160 mm.
[0053] Compared to coal briquettes, where about 10% by weight is usually added, a larger amount of binder is required. This is due to the higher porosity of biochar relative to coal. The cold compressive strength of each briquette was then measured. Twenty measurements were made on each briquette, pressed with an Adamel hydraulic press operating in the range of 0N to 2000N.
[0054] All measurements were between 1000 N and 2000 N, which are sufficient values to consider using these briquettes as a substitute for coke for charging into blast furnaces.
[0055] With the binder according to the invention, it is thus possible to produce biochar briquettes suitable for blast furnaces with a reduced environmental footprint.
[0056] Example 3
[0057] The first set of briquettes was prepared using the same briquetting process as in Example 2, wherein 90 wt% of coal was mixed with 10 wt% of a binder according to the invention having the same composition as the binder of Example 2.
[0058] A second set was prepared using the same briquetting process, wherein 90 wt% of coal was mixed with 10 wt% of petroleum bitumen as a binder (binder according to the prior art).
[0059] The cold compressive strength of each mass was then measured using the same machine as described in the previous examples.
[0060] The average value of the compressive strength of the briquettes produced with the binder according to the invention is 1890 N, which is higher than the average value of 650 N of the briquettes produced with the binder according to the prior art.
[0061] With the same amount of binder according to the invention as with prior art binders, briquettes with higher compressive strength can be prepared. This compressive strength is a key feature of briquettes for ensuring that they can be handled, transported or stored without deterioration.
[0062] Example 4
[0063] Iron briquettes were prepared using 8 wt% of a binder according to the invention and 92 wt% by weight of an iron ore concentrate containing 65.8 wt% of iron.
[0064] The binder used contained 85% by weight of pyrolysis oil from beech wood and 15% by weight of EPS.
[0065] The briquette properties were then analyzed and the iron content of the briquette was 63.3 wt%. For comparison, the iron content of briquette of sintered ore made from the same iron ore was 56 to 58 wt%. The cold strength of the briquette was high and exceeded 20 MPa, which ensured handling and charging in good conditions without the risk of briquette deterioration.
Claims
1. A binder for extrusion material, pelletized material, briquette material or agglomerated material, the binder comprising 80 to 90% by weight of pyrolysis oil produced by pyrolysis of biomass and 10 to 20% by weight of thermoplastic.
2. The adhesive according to claim 1, wherein the thermoplastic is selected from polyethylene, polystyrene, polycarbonate or styrene derivatives.
3. The adhesive according to claim 2, wherein the thermoplastic is expanded polystyrene.
4. The binder according to any one of claims 1 to 3, wherein the biomass is lignocellulosic biomass.
5. A method for producing a binder, comprising mixing and heating pyrolysis oil produced by pyrolysis of biomass with thermoplastics at a temperature of 150° C. to 220° C. in a ratio such that the binder contains 80% to 90% by weight of the pyrolysis oil and 10% to 20% by weight of the thermoplastics to produce the binder.
6. The method according to claim 5, wherein the pyrolysis of the biomass is carried out at a temperature of 450°C to 700°C.
7. The method for producing a binder according to claim 5 or 6, comprising the following steps: a. pyrolysis of biomass to produce biochar and pyrolysis oil, b. removing water from the pyrolysis oil so that the final water content in the dehydrated pyrolysis oil is less than 5% by weight, c. mixing the dehydrated pyrolysis oil with a thermoplastic in such a ratio to produce a binder that the binder contains 80 to 90 wt % of the dehydrated pyrolysis oil and 10 to 20 wt % of the thermoplastic.
8. The process of claim 7, wherein the water removal step is selected from the group consisting of a decantation step, a fractional condensation step, and a fractional crystallization step.
9. The method according to claim 7 or 8, wherein after the water removal step, the dehydrated pyrolysis oil is subjected to a decarbonization step before mixing with the thermoplastic.
10. A method according to any one of claims 5 to 9, wherein the thermoplastic is densified before mixing.
11. A method according to any one of claims 5 to 10, wherein the hot binder is cast in a mould to produce a binder ingot.
12. A method for producing agglomerates, comprising the following steps: At least one material is mixed with a binder according to any one of claims 1 to 4, and the mixture is subjected to a compression step to form a mass.
13. The manufacturing method of claim 12, wherein the at least one material is selected from coking coal, biochar, iron ore or steelmaking by-products. The manufacturing method according to claim 13 , wherein the material is biochar.
15. The manufacturing method according to claim 13, wherein the material is rolling mill sludge.
16. A raw material comprising the binder according to any one of claims 1 to 4 and at least one material selected from coking coal, biochar, iron ore or steelmaking by-products.
Citation Information
Patent Citations
Method for manufacturing binder for molded body, molded coal and coke and binder for molded body, molded coal, and coke
JP2018165301A
Chemical densification and reclamation of polystyrene
WO1998023672A1